Bibliometric analysis with VOS Viewer of journal trends in risk management, firm performance, and firm value - Listya, Khanti; Dwi Jati, Fatma; Asrin Jazuli, Muhammad (Jurnal Mantik, 2024)
Risk management that can be implemented optimally will help companies map risks. Risks that the company can adequately overcome will undoubtedly make the company's business processes run well, which is characterized by good company pro forma (performance). Company performance includes many aspects of a company, especially financial aspects. This improved company performance will undoubtedly be related to the company's value. Thus, there is a relationship between risk management, company performance, and company value, so it needs to be analyzed more deeply and thoroughly, one of which is by bibliometric analysis. The method combines convergent parallel types (Convergent Parallel Mixed Methods). Researchers collected quantitative data in the form of 500 publications from 2007-2022 with the PoP (Perish or Publish) application, and the data was tidied up with Mendeley Desktop and then carried out bibliometric analysis with VOSviewer software to produce visual displays, namely Network Visualization, Overlay Visualization, and Density Visualization. The visual display shows colourful lines interconnected to form a network that shows the relationship of publication citations between one another and nodes of varying colours and sizes that indicate the number of citations. The results of the analysis of publications on Risk Management, Company Performance, and company value show there are several other topics outside of these variables interconnected, consisting of 8 clusters. Each cluster consists of several issues and publications connected, as seen from the network on Network Visualization, Overlay Visualization, and Density Visualization